2019
DOI: 10.1177/0145445519834637
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rules and Feedback on Classroom Behavior of Adolescents in a Residential Treatment Setting

Abstract: Over the past 30 years, researchers have shown that various types of group contingency procedures can decrease problem behavior displayed by young children in academic settings. Recently, researchers have demonstrated that presession rules, within-session feedback, and interdependent group contingencies (i.e., contingently delivered tangible and edible items) increased appropriate behavior displayed by detained adolescents in a residential treatment facility. Nevertheless, it is possible that rules with feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…Help parents establish clear expectations. Research demonstrates that providing verbal and visual reminders of rules can increase appropriate behavior at the level of the individual (e.g., Faul, Stepensky, & Simonsen, 2012;Moore et al, 2019) and at the level of the group (e.g., Chinnappan, Rapp, & Burkhart, 2019;Hamrick, Richling, Brogan, Rapp, & Davis, in press) in classroom settings. Together, these studies provide evidence that rules can help decrease problem behavior across various populations.…”
Section: Promote the Use Of Schedules And Routinesmentioning
confidence: 99%
“…Help parents establish clear expectations. Research demonstrates that providing verbal and visual reminders of rules can increase appropriate behavior at the level of the individual (e.g., Faul, Stepensky, & Simonsen, 2012;Moore et al, 2019) and at the level of the group (e.g., Chinnappan, Rapp, & Burkhart, 2019;Hamrick, Richling, Brogan, Rapp, & Davis, in press) in classroom settings. Together, these studies provide evidence that rules can help decrease problem behavior across various populations.…”
Section: Promote the Use Of Schedules And Routinesmentioning
confidence: 99%
“…The absence of this component likely makes the procedure safer for both participants and practitioners. Finally, this study contributes to the growing body of research on the utility of behavior analytic procedures for adolescents receiving treatment in residential detention facilities (Brogan, Falligant, & Rapp, 2017;Chinnappan et al, 2019;McDougale et al, 2019;Niedfeld et al, 2019). Specifically, results of this study and those from the Neidfeld et al ( 2019) study have important clinical implications because each demonstrated that ABA practitioners could modify procedures developed for children with ASD and apply those procedures to problems displayed by adolescents in a juvenile residential facility.…”
Section: Discussionmentioning
confidence: 74%
“…Future research should also compare the effects of resetting and nonresetting behavior contracts. Given the positive effects using rules, alone or in combination with consequent interventions, reported by multiple studies of group procedures with adolescents in juvenile residential facilities (Brogan, Falligant, & Rapp, 2017; Chinnappan, Rapp, & Burkhart, 2019; Hamrick, Richling, Brogan, Rapp, & Davis, 2020; McDougale et al, 2019), future studies should also evaluate the effects of behavior contracts that involve two or more participants. To address these questions, researchers can employ the procedures outlined by Hagopian (2020) for analysis of data sets in both planned and retrospective consecutive case studies.…”
Section: Discussionmentioning
confidence: 99%